An Illustrated Guide to the Imaging Evolution of COVID in Non-Epidemic Areas of Southeast China - Wang, Lihua; Jiaerken, Yeerfan; Li, Qian; Huang, Peiyu; Shen, Zhujing; Zhao, Tongtong; Zheng, Hanpeng; Ji, Wenbin; Gao, Yuantong; Xia, Junli; Cheng, Jianmin; Ma, Jianbing; et al. (Frontiers in Molecular Biosciences, 2021)
Abstract: Purpose: By analyzing the CT manifestations and evolution of COVID in non-epidemic areas of southeast China, analyzing the development abnormalities and accompany signs in the early and late stages of the disease. Methods:This retrospective and multi-center study included 1648 chest CT examinations from 693 patients with laboratory-confirmed COVID-19 infection from 16 hospitals of southeast China between January 19 and March 27, 2020. Six trained radiologists analyzed and recorded the distribution and location of the lesions in the CT images of these patients. The accompanying signs include crave-paving sign, bronchial wall thickening, microvascular thickening,bronchogram sign,fibrous lesions, and analyze the evolution of the above-mentioned manifestations over time. Result：There were 1500 positive findings in 1648 CT examinations of 693 patients; the average age of the patients was 46 years old, including 13 children; the proportion of women was 49%. Early CT manifestations are single or multiple nodular, patchy or flaky ground glass-like density shadows.The frequency of occurrence of ground glass shadows (47.27%), fibrous lesions (42.60%) and microvascular thickening (40.60%) was significantly higher than other signs. Ground-glass shadows increase and expand 3-7 days after the onset of symptoms. The distribution and location of lesions were not significantly related to the appearance time. Ground glass shadows is the most common lesion with an average absorption time of 6.2 days, followed by consolidation, with an absorption time of about 6.3 days. It takes pure ground glass lesions about 8 days to absorb. Consolidation change into ground glass or pure ground glass takes 10-14 days; For ground glass opacity evolved into pure ground glass lesions takes an average 17 days. Ground-glass lesions evolve into consolidation takes 7 days, pure ground-glass lesions evolve into ground-glass lesions need 8 days. The average time for CT signs to improve is 10-15 days, the first to improve is the crazy paving sign and nodules; while the progression time is 6-12 days, seen in air bronchogram, bronchial wall thickening and bronchiectasis. Conclusion：This study depicts the CT manifestation and evolution of COVID in non-epidemic origin areas, and provides valuable first-hand information for clinical diagnosis and judgment of patient's disease evolution and prediction.